2017
DOI: 10.1002/ppap.201700174
|View full text |Cite
|
Sign up to set email alerts
|

Plasma agriculture: A rapidly emerging field

Abstract: Obtaining high yields in agricultural production is essential due to the world's population growth and increased food demand. At the same time, adverse effects of agriculture on the environment need to be kept to a minimum. Low temperature plasmas (LTPs) show promise as efficient green technologies for enhancing productivity while maintaining good food quality and safety in the many steps of the food cycle. As a result, applications of LTPs in agriculture have led to creation of a new, rapidly developing field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
127
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 218 publications
(140 citation statements)
references
References 33 publications
2
127
1
Order By: Relevance
“…It can be generated by various kinds of electrical discharges and it is often utilized in numerous environmental and biomedical applications . Recently, the CP has also found its applications in food processing, packaging, and agriculture …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be generated by various kinds of electrical discharges and it is often utilized in numerous environmental and biomedical applications . Recently, the CP has also found its applications in food processing, packaging, and agriculture …”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Recently, the CP has also found its applications in food processing, packaging, and agriculture. [12][13][14] The application of the CP in agriculture is either direct (seeds or plants are in a direct contact with plasma) or indirect (seeds or plants are exposed to plasma treated/activated gas or water). [14] The plasma in direct contact with the seed can stimulate its germination and growth [15][16][17][18] and subsequent fruit yield, [19] change enzymatic activity in developing seeds, [20][21][22] change secondary metabolites content, [23,24] and also reduce phytopathogenic microflora from the seed surface.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] The success of the low-pressure and atmospheric pressure nonthermal discharge plasmas in biomedicine led to the broadening of the field of applications, such as agriculture and food processing. [22][23][24][25][26] In the field of agriculture, research, first of all, focused on the improvement of seed germination and plant growth and cleaning from pathogens by the gas phase plasma species, such as the •OH radical, O 3 and NO molecules, O atoms, and UV radiation. [27][28][29][30][31][32] Recently, plasma-activated water (PAW) has become one of the main areas of interest in the field of plasma agriculture, as contact of seeds and plants with water is most natural.…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial property and plant growth enhancement were simultaneously obtained when plasma-activated L-Phe was used.We found that the benzene ring structure in solution contributed to antimicrobial property.Further, colony forming unit assay indicated that 99% of Escherichia coli (E. coli) were eliminated after 24-h incubation and radish sprout growth increased by about 40% after 2 days of cultivation.bactericidal efficacy, benzene ring structure, oxygen radicals, plant growth, plasma agriculture Recently, nonequilibrium atmospheric pressure plasma, [1] hereafter plasma, has been utilized in a wide range of applications including biomedical, [2][3][4][5] food industry, and agriculture. [6][7][8][9] The basic purpose of the plasma in the applications is activation or inactivation of micro-organisms and/or cells. Related researches have reported their use in the sterilization of micro-organisms, [10][11][12][13][14][15][16][17][18] plant growth enhancement, [19][20][21][22] wound healing, [23][24][25] and cancer therapy.…”
mentioning
confidence: 99%